Proceedings of the Common Council of the City of Saint Paul 133 (1891) - (:unkn) unknown (My University, 1891)
Ordinance no. 1507, § 6: Prohibited the carry of firearms, shooting of birds, or throwing of stones or other missiles within the park
Keywords: CARRY - CERTAIN PUBLIC PLACES